EGG PRODUCTION AND HATCHABILITY OF LOCAL DUCKS UNDER SEMI INTENSIVE VS EXTENSIVE MANAGEMENTS - Widiyaningrum, P.; Lisdiana, L.; Utami, N. R. (Diponegoro University, 2016)
The study aimed to compare the egg production and hatchability of local ducks under different management systems, namely semi-intensive and extensive. The research conducted was an experimental one-way classification withtwo treatments.Each treatment used 15 male and 120 females (mating ratio 1:8), and ducks aged 13-14 months. Eggs production was recorded during three weeks period. About300 eggs were selected from each treatment to be hatched. Fertility was observedat 4th days of hatching process using egg candler. Data of eggs production, eggs weight, fertility,and hatchability were analyzed using unpaired two sample Student’s t-test. The results showed that average of egg weight, fertility and hatchability were notdifferent under two managementsystem, but egg production in the semi-intensive maintenance was significantly higher (P<0.05) thanthose inthe extensive system.Egg production in the semi-intensivewas 12.3% higher than those in the extensive.In conclusion, the semi-intensive system that is applied in this study the number of eggs production but did not affect the average of egg weight, fertility and hatchability.